2019
DOI: 10.1002/anie.201902235
|View full text |Cite
|
Sign up to set email alerts
|

A Purified, Solvent‐Intercalated Precursor Complex for Wide‐Process‐Window Fabrication of Efficient Perovskite Solar Cells and Modules

Abstract: Ah igh-purity methylammonium lead iodide complex with intercalated dimethylformamide (DMF) molecules, CH 3 NH 3 PbI 3 ·DMF,i si ntroduced as an effective precursor material for fabricating high-quality solution-processed perovskite layers.S pin-coated films of the solvent-intercalated complex dissolved in pure dimethyl sulfoxide (DMSO) yielded thick, dense perovskite layers after thermal annealing.The low volatility of the pure DMSO solvent extended the allowable time for low-speed spin programs and considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…According to classical nucleation theory, perovskite crystallization from a precursor solution is only expected to occur upon reaching supersaturation. As mentioned in Section , the most common solvents used to prepare perovskite precursor solution, including DMF and DMSO, have the high boiling point and low saturated vapor pressure (see Table ), making them difficult to rapidly evaporate from the wet precursor thin films during perovskite crystallization . As a result, residual solvent molecules undergo secondary bonding with solutes,9,13d,31,38 which degrades the crystal morphology and causes poor coverage of the thin films.…”
Section: Controlling Precursor Solution Characteristics For Perovskitmentioning
confidence: 99%
“…According to classical nucleation theory, perovskite crystallization from a precursor solution is only expected to occur upon reaching supersaturation. As mentioned in Section , the most common solvents used to prepare perovskite precursor solution, including DMF and DMSO, have the high boiling point and low saturated vapor pressure (see Table ), making them difficult to rapidly evaporate from the wet precursor thin films during perovskite crystallization . As a result, residual solvent molecules undergo secondary bonding with solutes,9,13d,31,38 which degrades the crystal morphology and causes poor coverage of the thin films.…”
Section: Controlling Precursor Solution Characteristics For Perovskitmentioning
confidence: 99%
“…Further research indicated that the intermediate phase was actually MA 2 Pb 3 I 8 (DMSO) 2 with nonstoichiometric ratio of MAI and PbI 2 . A more recently report by Ozaki et al showed that CH 3 NH 3 I was excluded from the complex when recrystallizing from CH 3 NH 3 I and PbI 2 in DMSO solution . Zuo et al developed a vapor induced intermediate phase (VIP) strategy to manipulate the morphology of perovskite films .…”
Section: Modulating Morphologymentioning
confidence: 99%
“…Varying the concentration of high‐ D N additives in precursor solutions tunes the strength of lead‐solvent interactions, so as to fine‐control the crystallization and perovskite morphology (Figure 2b,c). [ 74–76 ] Due to the strong coordination of NMP and PbI 2 , Bu et al were able to inhibit the perovskite crystal growth by formation of PbI 2 •NMP adducts instead of perovskite‐DMF crystals in the perovskite precursor solution. The PbI 2 •NMP adducts have a much higher nucleation rate, allowing them to form a dense film, which then reacts in situ with embedded FAI/CsI to directly form α‐phase perovskite, bypassing the δ‐phase.…”
Section: Fabrication Of Large‐area Perovskite Filmsmentioning
confidence: 99%